Archives on Stage. New Forms of Valorising the Archive: From Communication to the Catwalk Stage - Vittorio Linfante (ZoneModa Journal)
In recent years, the archive has evolved from an endless source of research and innovation to the establishment of the brand’s heritage. It is increasingly evolving as a communication tool that takes on multiple forms, hovering between market and staging, between cultural events and media events. In the early 2000s, the red carpets were already defined as the ideal catwalk on which archive clothes could be worn, opening up the concept of the vintage, which expanded from a niche to the mass market, and the archive became a moment of sharing the history of the brand as well as a moment of communication. Thus, in this continuous game of cross-references, even the catwalks — historically deputed to the presentation of new products on the market — become places that stage the company’s archive. In this contest, the catwalks are not only the place to present new collections but have also become one of the places to stage, share and valorise the archive, increasingly integrating heritage and new collections in the exact moment and action: the archives, then, as “living machines” increasingly cohesive with the brand’s contemporaneity, which also finds in the fashion shows an opportunity to generate knowledge and even engage new markets.